Histomorphoiogical observations on buffalo oesophagus during prenatal development - BAWA, B S; ROY, K S; SINGH, OPINDER; UPPAL, VARINDER; MALHOTRA, VANEET (The Indian Journal of Animal Sciences, 2014)
The study was conducted on prenatal development of buffalo oesophagus in 20 foetuses ranging from 5.5 cm-60.1 cm crown rump length (CRL). Up to 7.5 cm CRL state lamina epithelial is was 2 layered, having basal layer of cuboidal cells and superficial layer of columnar cells. Superficial cells became polygonal and polyhedral at 11.2 cm CRL. Transformation to squamous cells was observed at 38 cm CRL. The lamina muscularis mucosae was in form of sheet at 11.2 em CRL stage. Bundle formation occurred at 28 cm CRL. The tunica submucosa had mesenchymal cells up to 11.2 CRL which differentiated into collagen and reticular fibres at 14.7 cm CRL stage. At 5.5 em CRL stage tunica muscularis had single layer of circularly oriented smooth muscle cells. The outer layer appeared at 11.2 cm CRL stage. Instead of usual pattern of inner circular and outer longitudinal orientation, the reverse pattern of muscles fibres viz. inner longitudinal and outer circular was observed. Skeletal muscle was observed at 11.2 cm CRL at cranial end and at 20 cm CRL stage in the caudal end.